In Memoriam: Hana Havelkova - Sokolova, Vera (Gender a vyzkum / Gender and Research, 2021)
Hana Havelkova (1949-2020) was one of the most influential figures of her generation. An internationally renowned thinker and the author of more than seventy publications in Czech, English, and German, she formulated many original and complex arguments about feminist political philosophy, gender theory of culture and society, feminist epistemology, women in science, and the representation of women in politics, media,and public discourse. After the Velvet Revolution, she significantly enriched feminist theorising between 'East' and 'West', helped to create the conceptual apparatus for a gender analysis of state socialism, participated in oral history research of experiences of women during and after socialism. The thematic breath and analytical depth of Hana Havelkova's scholarship is impressive and remains unparalleled within Czech feminist sociology.